Challenges to the Adoption of Deep Eutectic Solvents in the Electrodeposition Industries - T. A. Green; S. Roy (ECS Advances)
In the past 20 years there has been a considerable interest in the application of deep eutectic solvents (DESs) for metal finishing applications and a large number of academic studies have been performed related to electrodeposition, electroless deposition and electropolishing. These DES materials possess a number of unique characteristics and it was predicted that they would replace hazardous and toxic materials associated with many aqueous-based processes and make them inherently greener and more sustainable. They would also facilitate the deposition of metals and alloys that are difficult or impossible to deposit from aqueous solutions. However, until now there have only been limited demonstrations of scaled-up processes, and their commercialisation and deployment in the metal finishing industries has not eventuated. In this paper we reflect on some of the reasons why and identify some key limitations of DES-based surface finishing processes. Unless these barriers can be overcome, it will be difficult for DESs to be adopted in these industries.